Nuclear accumulation of β-catenin protein indicates activation of wnt signaling in chemically induced rat nephroblastomas - Ehrlich, David Hans Wolf; Bruder, Elisabeth; Thome, Martin Andreas; Gutt, Carsten N.; Knebel Doeberitz, Magnus von; Niggli, Felix; Perantoni, Alan O.; Koesters, Robert (Pediatric and developmental pathology, 2010)
Aberrant wnt signaling caused by mutations in CTNNB1 occurs in about 15% of Wilms tumors, and these mutations appear to be dependent on the concomitant mutational inactivation of the zinc-finger protein WT1. Nuclear ?-catenin protein, a substitute marker of active wnt signaling, has been detected in an even higher proportion (>50%) of Wilms tumors, suggesting alternative genetic pathways leading to ?-catenin activation. Thus, targeting wnt signaling may become an important future therapeutic strategy in Wilms tumor patients. Currently, chemically induced rat nephroblastomas provide the only available rodent model for this tumor. To determine the contribution of active wnt signaling in this model, we investigated 24 chemically induced rat nephroblastomas for ?-catenin protein expression and for Ctnnb1 and WT1 mutations. Immunohistochemistry showed focal strong nuclear accumulation of ?-catenin protein in 18 of 24 tumors, although in a heterogenous pattern. Blastemal and mesenchymal compartments displayed nuclear-positive cells more frequently than areas of epithelial differentiation. Interestingly, we found no mutation of exon 3 of Ctnnb1 and no mutation within the zinc-finger region of WT1 in any of the 24 tumors analyzed. In conclusion, our findings suggest activation of wnt signaling in the majority (63%) of chemically induced rat nephroblastomas. Nuclear expression of ?-catenin in the absence of Ctnnb1 mutations implies, however, alternate mutational targets in rat nephroblastomas.